Using British Literature to Teach Empathy to the Chinese University Students Majoring in English - He, Huan; Amini, Mansour; Wu, Yanan (International Journal of Academic Research in Progressive Education and Development, 2023)
This paper aims to strengthen Chinese University English Majors’ (CUEMs) capability in understanding, analyzing, and appreciating British Literature. This research focuses on the effective pedagogy applied to make CUEMs compassionate and empathetic. The participants were 65 students who were in their third year of study at the School of Foreign Languages, in Sichuan University of Science & Engineering, a Chinese University and could sympathize with feelings and emotions expressed by British authors, showing mastery of British literary writings. Facing exotic literature, CUEMs usually feel perplexed and stressed, then they give the cold shoulder to the course as well their teaching staff. The empathy empowerment program adopted a qualitative research design, acquiring textual data gained from the learners who were asked to hand in their essays particularly assigned by the researcher to perceive whether the learners become empathetic after learning some British literary writings. After the collected data were coded and analyzed, the program testified that learners became empathetic after taking British literature classes through thematic analysis. This research can be valuable for literature academics both in and outside of China who are frequently confused, helpless, and even frustrated in teaching literature and are eager to get more responses from their learners in class by learning to assign meaningful and thought-provoking, empathy-arousing essay questions highly associated with literary texts to their learners and scrutinizing their essays, then an active communication between academic and learners can be successfully made.